2006
DOI: 10.1111/j.1471-4159.2006.04080.x
|View full text |Cite
|
Sign up to set email alerts
|

A rapid exocytosis mode in chromaffin cells with a neuronal phenotype

Abstract: We have used astrocyte-conditioned medium (ACM) to promote the transdifferentiation of bovine chromaffin cells and study modifications in the exocytotic process when these cells acquire a neuronal phenotype. In the ACM-promoted neuronal phenotype, secretory vesicles and intracellular Ca 2+ rise were preferentially distributed in the neurite terminals. Using amperometry, we observed that the exocytotic events also occurred mainly in the neurite terminals, wherein the individual exocytotic events had smaller qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…The exocytotic release of catecholamines was detected by amperometry, as previously described (Ardiles et al, 2006). Carbon fibers of 5 m radius (Thornel P-55, Amoco) were used to manufacture the microelectrodes (Kawagoe et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…The exocytotic release of catecholamines was detected by amperometry, as previously described (Ardiles et al, 2006). Carbon fibers of 5 m radius (Thornel P-55, Amoco) were used to manufacture the microelectrodes (Kawagoe et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, exocytosis is largely delayed in the presence of cross-linking agents like glutaraldehyde or formaldehyde that should freeze the dissociation of catecholamines from Cgs (Borges et al 2000). Moreover, in experiments on chromaffin cells cultured in astrocyte conditioned media, the phenotype of the chromaffin cells switches to a neuronal-like form observed with electron microscopy that exhibited many small vesicles containing little dense material (Ardiles et al 2006). Using amperometry, these authors observed a drastically accelerated exocytosis suggesting a close relationship between the presence of vesicular matrix and the kinetics of exocytosis.…”
Section: The Release Of Catecholamines From the Ldcv During Exocytosimentioning
confidence: 95%
“…Alternatively, other groups suggest a preferential role of some channel subtype in close proximity to the secretory sites (Lopez et al 1994;Artalejo et al 1994;Lara et al 1998;O'Farrel and Marley 2000;Albillos et al 2000) and a further role of mitochondria in sequestering Ca 2+ entering through Ca 2+ channels (Ales et al 2005). In addition to this, the eYciency of stimulus-secretion coupling can be altered in many ways, some relevant examples are: (1) PKC activation, which enhances exocytosis (Gillis et al 1996), (2) rapid and sustained increase of intracellular cAMP, which potentiates Ltype channel densities and secretion at diVerent proportions , (3) transdiVerentiation of chromaYn cells with astrocyte-conditioned medium, which promotes the acquisition of a neuronal phenotype and accelerates the exocytotic kinetics, by a better coupling between secretory vesicles and Ca 2+ channels (Ardiles et al 2006) and (4) -adrenergic stimulation, which enhances the stimulus-secretion coupling of Ltype Ca 2+ channels by repeated action potential-like stimulations (Polo-Parada et al 2006).…”
Section: Introductionmentioning
confidence: 99%